Photovoltaics- the ultimate energy solution - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Khairu Aidilnishah, Rizan Jalil; Mohd Asyrak, Deraman; Rajan, Jose; Aziah, Mohd Yusoff (Penerbit UMP, 2009)
Alternate energy sources are actively sought in light of rising energy demand and depleting oil resources.